Analisis Permeabilitas Menggunakan Metode Falling head pada Tanah dengan Penambahan Abu Serabut Kelapa - Sisilia Mira Tangdiombo; Benyamin Tanan; Irwan Lie Keng Wong (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This study was to determine the physical properties of the soil and the effect of adding coconut ash to the permeability coefficient using the fall method. Soil sampling was carried out in Bolu Village, Rantepao District, North Toraja Regency and the added material used coconut fiber from community waste located on Biring Romang Street, Kapasa Village, Makassar City with the proportion of added material being 0%, 5%, 10%, and 15%. The structure in this research is to use research on the physical properties of the soil and then compile the composition of the alloy to the soil permeability test so that it can produce a coefficient of soil permeability. The results of this study indicate that the soil meets the characteristics as clay soil. The effect of adding fiber ash to the soil is a decrease in the permeability value where the higher the proportion of coconut fibers, the smaller the permeability until the addition of 15%.